Identifying pathogenicity-related genes in the pathogen Colletotrichum magnum causing watermelon anthracnose disease via T-DNA insertion mutagenesis - Guo, Zhen; Wu, Huijie; Peng, Bin; Kang, Baoshan; Liu, Liming; Luo, Chaoxi; Gu, Qinsheng (Frontiers in Microbiology, 2023)
Colletotrichum magnum is a crucial watermelon disease threatening the production and quality. To understand the pathogenic mechanism of C. magnum, we optimized the Agrobacterium tumefaciens-mediated transformation system (ATMT) for genetic transformation of C. magnum. The transformation efficiency of ATMT was an average of around 245 transformants per 100 million conidia. Southern blot analysis indicated that approximately 75% of the mutants contained a single copy of T-DNA. Pathogenicity test revealed that three mutants completely lost pathogenicity. The T-DNA integration sites (TISs) of three mutants were Identified. In mutant Cm699, the TISs were found in the intron region of the gene, which encoded a protein containing AP-2 complex subunit σ, and simultaneous gene deletions were observed. Two deleted genes encoded the transcription initiation protein SPT3 and a hypothetical protein, respectively. In mutant Cm854, the TISs were found in the 5′-flanking regions of a gene that was similar to the MYO5 encoding Myosin I of Pyricularia oryzae (78%). In mutant Cm1078, the T-DNA was integrated into the exon regions of two adjacent genes. One was 5′-3′ exoribonuclease 1 encoding gene while the other encoded a WD-repeat protein retinoblastoma binding protein 4, the homolog of the MSl1 of Saccharomyces cerevisiae.